Effect of nitrogen limitation on biochemical composition and photosynthetic performance for fed-batch mixotrophic cultivation of microalga Spirulina platensis. (September 2018) - Li, Xiaoting; Li, Wei; Zhai, Jun; Wei, Haoxuan
Highlights: Microalgal biomass productivity was enhanced by mixotrophic culture. Continuous accumulation of carbohydrates was achieved by nitrogen limitation. More pigments were degraded for maintaining algal growth in mixotrophic culture. Mixotrophy amplified side-effect of nitrogen stress on photosynthetic activity. Abstract: In this study, the effect of nitrogen limitation on microalgal growth, biochemical composition and photosynthetic performance was investigated in fed-batch mixotrophic cultivation of microalga Spirulina platensis, compared with that in autotrophic cultivation. The microalgal biomass productivity was greatly enhanced by mixotrophic cultivation. With nitrogen limitation, the mixotrophic culture accelerated the degradation of microalgal pigments and proteins to supply intracellular nitrogen for maintaining higher biomass productivity, simultaneously accumulating more carbohydrates. The mixotrophic cultivation amplified the adverse effect of nitrogen limitation on the microalgal photosynthetic performance in comparison with autotrophic cultivation. This fed-batch mixotrophic cultivation is an effective strategy for enhancing biomass productivity and total carbohydrates yield under nitrogen limited conditions.